Penyusunan Administrasi Pembelajaran Pendidikan Agama Islam - Irman Sumantri (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2021)
This Community Service Program (PKM) is carried out with the aim of providing a conceptual understanding and implementation of the preparation of learning administration. The implementation of PKM is carried out by socialization and simulation methods. The results obtained at the time of socialization, that the teacher understood the concept of the preparation of learning administration in the subjects of Islamic religious education at the elementary school level. In addition, the participants or the teacher council who attended the activity were able to arrange learning administration. Thus it can be concluded that, community service activities entitled the preparation of Islamic religious education learning administration run smoothly and effectively.